Increasing use of non-invasive ventilation in asthma: a long-term analysis of the Portuguese national hospitalization database. (December 2014) - Alves, Daniela; Freitas, Alberto S.; Jacinto, T.; Vaz, Manuel S.; Lopes, Fernando O.; Fonseca, João A.
Abstract Objectives: To describe the use and outcomes of non-invasive positive pressure ventilation (NPPV) and invasive ventilation (IV) in adults hospitalized for acute asthma exacerbations in Portugal. Methods: We analyzed the hospitalizations of adults with a principal diagnosis of asthma in mainland Portugal between 2000 and 2010. The data source was the national hospitalizations database, which includes administrative and clinical data produced by physicians trained in coding. Results: Ventilation support was used in 5.1% (n = 747) of the 14 515 hospitalizations with a principal diagnosis of asthma: NPPV in 1.7% (n = 241) and IV in 3.5% (n = 506); NPPV use increased from 1% in 2000 to 3.3% in 2010. In patients with asthma, the ratio of NPPV use to IV use increased from 0.27 to 1.06. This increase was observed even after exclusion of secondary diagnoses in which NPPV is frequently used. The mortality rate was 1.5% for all asthma hospitalizations: 2.5% when NPPV was used and 15.8% for those requiring IV. Conclusions: The use of ventilation support in asthma remained stable over time; however, the use of non-invasive ventilation has increased. Still, we do not have good data regarding the effectiveness of non-invasive ventilation when treating asthma exacerbations. Therefore, additional studies are much needed and should assess physiologic and clinical variables that might affect the effectiveness of non-invasive ventilation in patients with asthma exacerbations.